Role of Administrators in Blended learning in Higher Education Institution - Fatima Muhammad Qassim; N.B. Jumani; Samina Malik (PJDOL, 2023)
As higher education institutions adopt blended learning, administrators play a crucial role in implementing and supporting blended learning, ensuring its success (Lomonosova & Valentinovna, 2018). The study investigates administrators' perceptions of blended learning as a teaching strategy, using a proportionate sampling sample and a content validity instrument modified by an expert. The study involved 27 administrators respondents who were selected from the universities in Islamabad. The interview guide was created to assess administrators' readiness for blended learning, focusing on their awareness of facilities, finances, capacity-building initiatives, challenges, and technology capabilities. The reliability of the results was ensured by consistent patterns and plausible reasons for differences. Data analysis involved analyzing administrative attitudes through interviews, coding the data, and identifying recurring themes. The study concluded that despite the availability of resources and support, the studyemphasises the difficulties administrators encounter when implementing blended learning in higher education institutions. For blended learning to be successfully implemented, infrastructure facilities including well-equipped classrooms and high-speed internet connection are crucial.